Optimalisasi Kebijakan Pemanfaatan Lahan dengan Pola Mix Land Use Terhadap Perencanaan Prasarana Pendidikan dan Kesehatan di Kota Batam - Nurbaiti, Nurbaiti; Khoirunurrofik, Khoirunurrofik (Jurnal Kebijakan Ekonomi, 2015)
This research aims to identify the patterns of spatial use to optimize the use of space equal distribution of education and health well as see the effect of education and health infrastructure facilities to NJOP (land value). The results of this research identified more than 50% the use of space on Batam city turn toward adopt Mix Land Use with the characteristics are: 1) is a district with a high service hierarchy; 2) have the education and health infrastructure which is more spread equally to be accessible for the public; 3) The gap between education and health infrastructure are smaller. The existence of education and health infrastructure does not affect the formulation on the value of NJOP. The results of these studies, recommends for using Mix Land Use in polices of RTRW Batam City, and the need for reformulation of NJOP determination as the potential for increased Original Local Income (PAD) to account the effect of the existence of education and health infrastructure in each region.